Metallic Cylinder Reflected Power Measurement For 93.1GHz Frequency Modulated Continuous Wave Radar Calibration - Ja’afar, P. N.; Idrus, S. M.; Ambran, S.; Yusri, N. A.; Mohamed, N.; Hamzah, A.; Shibagaki, N.; Kashima, K.; Hayashi, T. (International Journal of Integrated Engineering, 2023)
A metallic cylinder is one of the best materials and shapes to calibrate a radar system performance. The measurement of a 4cm diameter and 3cm-height metallic cylinder as a target has been presented for the analysis at the millimeter-wave (mm-wave) spectrum. This experiment was conducted in a real airport environment at Kuala Lumpur International Airport considering clear sky conditions. The measurement was carried out at 93.1 GHz which uses Frequency Modulated Continuous Wave (FMCW) radar to consistently detect the target. The radar cross-section (RCS) of the metallic cylinder is measured with respect to the angle of runway pavement. It is found that the measurements exhibited smaller RCS value with an average of –43.47 dBsm at a longer range compared to –30.16 dBsm at a shorter range with a total change of 13.31 dBsm. The reflectivity characteristics of the radar target, theoretical measurement of the metallic cylinder, its incident angle from the radar target, and measurement evaluation are presented in this paper.